1995
DOI: 10.1074/jbc.270.26.15611
|View full text |Cite
|
Sign up to set email alerts
|

Lysine-based Structure in the Proregion of Procathepsin L Is the Recognition Site for Mannose Phosphorylation

Abstract: The recognition of lysosomal enzymes by UDP-GlcNAc: lysosomal-enzyme GlcNAc-1-phosphotransferase (phosphotransferase) is mediated by a protein structure on lysosomal enzymes. It has been previously demonstrated that lysine residues are required for phosphorylation of procathepsin L and are a common feature of the site on many lysosomal proteins. In this work, the procathepsin L recognition structure was further defined by identification of the region of the protein containing the structure and the critical lys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
52
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 32 publications
3
52
0
Order By: Relevance
“…VECTORSTAIN Elite ABC kit (Rabbit IgG), DAB substrate kit for peroxidase and Hematoxylin QS were purchased from Vector Laboratories. Rabbit anti-human cathepsin D serum (Cuozzo et al, 1998), affinity-purified rabbit anti-mouse cathepsin L antibodies (Cuozzo et al, 1995), and affinity-purified rabbit anti-bovine Man-6-P/IGF-2 receptor antibodies (Tao et al, 2001) were prepared as previously described.…”
Section: Cell Linementioning
confidence: 99%
“…VECTORSTAIN Elite ABC kit (Rabbit IgG), DAB substrate kit for peroxidase and Hematoxylin QS were purchased from Vector Laboratories. Rabbit anti-human cathepsin D serum (Cuozzo et al, 1998), affinity-purified rabbit anti-mouse cathepsin L antibodies (Cuozzo et al, 1995), and affinity-purified rabbit anti-bovine Man-6-P/IGF-2 receptor antibodies (Tao et al, 2001) were prepared as previously described.…”
Section: Cell Linementioning
confidence: 99%
“…A number of studies from our laboratory and others have shown that the protein recognition domain of acid hydrolases is a complex conformation-dependent determinant that includes a number of critical lysine residues (16)(17)(18)(19)(20)(21)(22)(23). On this basis, it seems likely that the interaction of an acid hydrolase with GlcNAc-1-phosphotransferase would involve multiple contacts between the surfaces of the two proteins.…”
mentioning
confidence: 99%
“…With intracellular proteases, this processing occurs in the lytic compartment (lysosomes or vacuoles) (15); with extracellular proteases, the processing occurs during secretion (16). Targeting to the correct compartment for processing is mediated by a peptide (17) or phosphomannose (18) targeting signal on the NH 2 -terminal precursor domain that is recognized by a specific receptor that is presumed to be localized in the Golgi apparatus (19,20) to target the protein to the activating compartment.…”
mentioning
confidence: 99%